2009
DOI: 10.1007/s11199-009-9593-9
|View full text |Cite
|
Sign up to set email alerts
|

Father Involvement in Immigrant and Ethnically Diverse Families from the Prenatal Period to the Second Year: Prediction and Mediating Mechanisms

Abstract: This longitudinal study focused on fathers' involvement from the prenatal period through infants' first year in Dominican immigrants (n=73), Mexican immigrants (n=65) and African Americans (n=66) residing in New York City. Fathers' prenatal involvement, the quality of the mother-father relationship, fathers' postnatal involvement with their 1-and 6 month olds and fathers' involvement with their 14 month-olds (i.e., time spent with infant; eating meals with infant; activities with infant) were examined. Father … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
43
0
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 42 publications
2
43
0
8
Order By: Relevance
“…Likewise, Updegraff et al (2009) found that Mexican-American mothers reported spending more time with their children, about whom they expressed greater warmth and acceptance than fathers did. Chuang and Su (2009), Cabrera et al (2009), and Tamis-LeMonda et al (2009 all observed that this distinction between maternal and paternal roles was established very early in the children's lives, with the quality of the relationship between the fathers and mothers molding dynamics even before the children were born, and prenatal involvement predicting postnatal involvement by immigrant fathers from Mexico and the Dominican Republic (Tamis-LeMonda et al 2009). …”
mentioning
confidence: 99%
“…Likewise, Updegraff et al (2009) found that Mexican-American mothers reported spending more time with their children, about whom they expressed greater warmth and acceptance than fathers did. Chuang and Su (2009), Cabrera et al (2009), and Tamis-LeMonda et al (2009 all observed that this distinction between maternal and paternal roles was established very early in the children's lives, with the quality of the relationship between the fathers and mothers molding dynamics even before the children were born, and prenatal involvement predicting postnatal involvement by immigrant fathers from Mexico and the Dominican Republic (Tamis-LeMonda et al 2009). …”
mentioning
confidence: 99%
“…Além disto, a responsabilização da mãe pelos cuidados do bebê também pode contribuir a ponto de ter pouco contato com o filho. Para além disto, a interação do pai com o bebê com um ano de vida pode estar também relacionada ao envolvimento do pai desde a gestação, e que vai se ampliando ao longo do tempo (Tamis-LeMonda, Kahana-Kalman, & Yoshikawa, 2009). Soma-se a isto o fato de os pais muitas vezes terem uma percepção de menor eficácia parental quando comparando à mãe (Ferreira et al, 2014 Mesmo existindo em nossa sociedade a tendência a uma atualização do papel paterno, que passou a ser mais participativo (Vieira et.…”
Section: Discussionunclassified
“…Public policies and intervention strategies need to focus on supporting Black unmarried resident fathers to maintain their initial level of engagement with young children over time. Given the evidence from past research that enhancing the quality of the mother-father relationship may improve later father engagement quality (Tamis-LeMonda et al, 2009), future research should also examine the extent to which unmarried resident fathers' relationship quality with their child's mothers affect father engagement change over time.…”
Section: Discussionmentioning
confidence: 99%
“…African American fathers are known as ethnic fathers who highly value their parental role within their family system characterized by a relatively equitable distribution of childcare responsibilities between mothers and fathers (Tamis-LeMonda, Kahana-Kalman, & Yoshikawa, 2009). Coley and Chase-Lansdale (1999) also indicated that the majority of African American fathers in their study showed high levels of engagement at the time of children's birth, during infancy, and when children were 3-year-old.…”
Section: Father Engagement and Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation